Bank Competition, Credit Risk, and Foreign Bank Penetration: Empirical Evidence from Indonesia - Olivia Nuralyza; Niluh Putu Dian Rosalina Handayani Narsa; Dewi Sriani (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2022)
This study examines the relationship between bank competition and credit risk with foreign bank penetration as a moderating variable. The research sample used was 79 commercial banks listed in the Indonesian Banking Directory published by the Financial Services Authority (OJK) during the 2014-2019 period with a total of 474 observations. The results of this study indicate that the higher the bank's competition, the higher the bank's credit risk, which is in accordance with the competition-fragility theory. Furthermore, from the results of the Moderated Regression Analysis, the results show that foreign bank penetration has not been able to moderate the relationship between bank competition and bank credit risk, however, if it stands as an independent variable on its own, foreign bank penetration will reduce bank credit risk. The results of this study contribute to providing useful information for parties in the banking industry that increasing foreign bank penetration can reduce bank credit risk.